"Open" and "closed" therapies: Psychotherapeutic relationship and variety in actions in different phases of therapies. (13th July 2020) - Voutilainen, Liisa; Peräkylä, Anssi
Abstract : Abstract As a longitudinal process, psychotherapy is geared to facilitate a positive change in the patients. Starting from the classical psychoanalytical tradition, a fundamental aim in many types of psychotherapy is to increase the clients' contact with their problematic emotions and parts of the self, and increase their self-reflexive abilities. As the interaction in psychotherapy aims towards a change, it is evident that it is not only the patient's inner experience that changes during the process of psychotherapy, but also the relationship between the participants develops over time. In this paper, we propose a way to describe the global dynamics of the therapist-patient interaction, by making a distinction between what we call open and closed therapies. This perspective emerged from our work with a set of data coming from five dyads of psychodynamic psychotherapy. We consider how much variety there is in the interactional moves of the participants, that is, in the possible relations between two turns at talk. We call therapies with sequential variation as "open therapies" and those with rather stable sequential patterns as "closed therapies". We propose that the variety on sequential relations links to the phasic organization that is common to all psychotherapeutic processes (in that they have beginning, middle and end) and to the change in the internal world of the patient.